2019
DOI: 10.3390/bioengineering7010003
|View full text |Cite
|
Sign up to set email alerts
|

Inoculum Source Determines Acetate and Lactate Production during Anaerobic Digestion of Sewage Sludge and Food Waste

Abstract: Acetate production from food waste or sewage sludge was evaluated in four semi-continuous anaerobic digestion processes. To examine the importance of inoculum and substrate for acid production, two different inoculum sources (a wastewater treatment plant (WWTP) and a co-digestion plant treating food and industry waste) and two common substrates (sewage sludge and food waste) were used in process operations. The processes were evaluated with regard to the efficiency of hydrolysis, acidogenesis, acetogenesis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…3 a). In previous investigations, this genus was associated with butyrate and acetate formation during mesophilic AD [ 34 ]. Moreover, Fastidiosipila spp.…”
Section: Discussionmentioning
confidence: 99%
“…3 a). In previous investigations, this genus was associated with butyrate and acetate formation during mesophilic AD [ 34 ]. Moreover, Fastidiosipila spp.…”
Section: Discussionmentioning
confidence: 99%
“…In general, no harmful elements were found in the inoculum, hence making it suitable to be used in the digestion process. Moestedt et al (2020) found that the inoculum sourced from the wastewater treatment plant for the anaerobic digestion process will produce higher acetate and lower lactate, when treating food waste co-digested with sewage sludge ( Moestedt et al, 2020 ). In comparison to elements found in this study, previous characteristic of the wastewater treatment inoculum shows that it also contained calcium, iron, molybdenum, aluminum, and phosphorus.…”
Section: Resultsmentioning
confidence: 99%
“…The complexity of the substrates seemed to exert an impact on Coulombic efficiency. Acetic acid contains two carbon atoms-it is a carbon-neutral source that must be hydrolyzed by electrogenic bacteria in order to generate electrons [23]. Sucrose (a 22-carbon compound) is a disaccharide that needs hydrolysis before it can be used by microorganisms, while many microbial species may uptake sucrose for assimilatory metabolism as well.…”
Section: Substrate Removal Current Power Density and Coulombic Efficiencymentioning
confidence: 99%